PENGENALAN SISTEM DATABASE : KONSEP DASAR DAN MANFAATNYA DALAM PERUSAHAAN - Intan Fahzirah; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
This journal discusses the introduction of database systems as well as the basic concepts and benefits for companies. Basic concepts include database definitions, tables, relationships between tables, and the SQL query language. The benefits of database systems for companies include efficiency in data management, increasing information accessibility, and supporting more timely decision making. With a good understanding of the basic concepts and benefits of database systems, companies can improve their productivity and service quality.